Linguistic relativity: object categorisation differences between Arabic and English speakers - Dawood, Abdullah; Sen, Maya G.; Yan, Jing Wu (Penerbit Universiti Kebangsaan Malaysia, 2020)
We examined the potential effects of the Arabic grammatical gender system on object categorisation using an online voice attribution task. Compared to native English speakers (including English monolinguals and English-Arabic bilinguals), native Arabic speakers (including Arabic monolinguals and Arabic-English bilinguals) were more likely to assign either a man’s voice (or a boy’s voice) or a woman’s voice (or a girl’s voice) to inanimate objects with a gender that was consistent with the objects’ grammatical gender in Arabic. Interestingly, when assigning genders to objects that do not have an associative stereotypical gender, a male-attribution tendency was found in both native Arabic speakers and native English speakers. Additionally, while native Arabic speakers and native English speakers assigned voices consistently with Arabic grammatical gender (GG) to objects with an associative stereotypical gender compatible with its grammatical gender in Arabic, they assigned voices to objects with an associative stereotypical gender incompatible with its grammatical gender in Arabic, likely based on object-gender stereotypical associations. Additionally, the performance of Arabic and English monolinguals was highly comparable with that of Arabic-English and English-Arabic bilinguals. We conclude that while the effects of linguistic structure on object categorisation might be generalised to Oriental languages, these effects are constrained and sometimes over-ridden by object-gender stereotypical associations, supporting a fully interactive account of the linguistic relativity hypothesis.